1997
DOI: 10.1055/s-2006-957631
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Oren-Gedoku-to and its Components on Cholesteryl Ester Synthesis in Cultured Human Hepatocyte HepG2 Cells: Evidence from the Cultured Hep2G Cells andIn VitroAssay of ACAT

Abstract: The pharmacological effects of Oren-gedoku-to (OGT), a Japanese-Chinese traditional herbal medicinal mixture on lipid biosynthesis were investigated in cultured human hepatocyte HepG2 cells. The addition of OGT (0.5 and 4.2 mg/ml), which had no effect on cell proliferation and cellular protein content, caused a marked decrease in the cellular cholesterol content, particularly cholesteryl ester content following 24 h incubation. The incorporation of 14C-oleate into cellular cholesteryl ester fraction was also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 2 publications
(4 reference statements)
0
11
0
2
Order By: Relevance
“…Therefore, inhibition of hepatic ACAT may be the mechanism whereby naringenin exerts its hypocholesterolemic effects. Inhibition of hepatic ACAT has also been demonstrated for a flavonoid structurally different from naringenin, baicalein (IC 50 of approximately 100 M in isolated rat hepatic microsomes) (96). Whether reduced apoB secretion and inhibition of ACAT activity are general features of flavonoids remains to be determined.…”
Section: Lipid and Lipoprotein Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibition of hepatic ACAT may be the mechanism whereby naringenin exerts its hypocholesterolemic effects. Inhibition of hepatic ACAT has also been demonstrated for a flavonoid structurally different from naringenin, baicalein (IC 50 of approximately 100 M in isolated rat hepatic microsomes) (96). Whether reduced apoB secretion and inhibition of ACAT activity are general features of flavonoids remains to be determined.…”
Section: Lipid and Lipoprotein Metabolismmentioning
confidence: 99%
“…While the majority of research has focused on the antioxidant roles of flavonoids, a number of reports have suggested that these compounds may also influence atherogenesis through an effect on lipid and lipoprotein metabolism (4,8,10,14,15,51,88,94,96). Investigation of naturally occurring compounds as regulators of triglyceride and cholesterol metabolism has particular therapeutic importance, as evidenced by the discovery of the first HMG-CoA reductase inhibitors derived from fungal fermentation products, which are now widely used for the treatment of hyperlipidemia.…”
Section: Lipid and Lipoprotein Metabolismmentioning
confidence: 99%
“…Huang-Lian-Jie-Du (Oren-geduku-to) decoction is a well-known preparation officially listed in the Chinese Pharmacopoeia (2000 edition), which has been used in treatment of diabetes mellitus (Lu et al, 2002), hyperlipemia (Yotsumoto et al, 1997;Kim et al, 2002), atherosclerosis (Sekiya et al, 2005), gastroinrestinal disorders (Ohta et al, 1999), hepatitis (Lin et al, 1996a,b), cardiovascular diseases (Xu et al, 2000) and ischemia-reperfusion brain injury (Hwang et al, 2002), for its anti-oxidant, anti-inflammatory, hypoglycemic, hypocholesterolemic, antiviral, hepato-protective and anti-bacterial activities and protective effect against impairment of learning and memory induced by transient cerebral ischemia. This compound prescription consists of Coptis Rhizoma, Gardenia fructus, Phellodendron cortex and Scutellaria radix.…”
Section: Introductionmentioning
confidence: 99%
“…ํ˜ˆ๊ด€ ๋‚ดํ”ผ์„ธํฌ์˜ ์†์ƒ์€ ์„ธํฌ ์œ ์ฐฉ ๋ถ„์ž (cell adhesion molecules)์™€ ๊ฐ™์€ ๋ถ„์ž์™€ ํ˜ˆ๊ด€์ˆ˜์ถ•์ธ์ž์ธ endothelin-1 (ET-1)๊ณผ ๊ฐ™์€ ๋ถ„์ž๋“ค์„ ๋ฐœํ˜„ ์ฆ๊ฐ€๋ฅผ ์œ ๋„ํ•˜์—ฌ ํ˜ˆ๊ด€ ๋‚ดํ”ผ ์„ธ ํฌ ๊ธฐ๋Šฅ ์ €ํ•˜ ๋ฐ ์กฐ์ง์†์ƒ์„ ๋ถˆ๋Ÿฌ์™€ ํ˜ˆ๊ด€์—ผ์ฆ ๋ฐ ๊ณ ํ˜ˆ์••์„ ์œ  ๋ฐœํ•˜๊ฒŒ ๋œ๋‹ค 4) . ์ตœ๊ทผ์—๋Š” ์ด๋Ÿฌํ•œ ๋Œ€์‚ฌ์„ฑ ์งˆํ™˜์€ ์น˜๋ฃŒ๋ณด๋‹ค ์˜ˆ๋ฐฉ์ด ํ•„์š”ํ•œ ์งˆํ™˜์œผ๋กœ ์—ฌ๊ฒจ์ ธ, ๊ณ ์ง€ํ˜ˆ์ฆ, ๊ณ ํ˜ˆ์••, ๊ทธ๋ฆฌ๊ณ  ๋‹น๋‡จ๋ณ‘ ๋“ฑ์„ ์˜ˆ ๋ฐฉํ•˜๊ณ  ์ €ํ•ดํ•˜๋Š” ๊ฐ์ข… ์ƒ๋ฆฌํ™œ์„ฑ ๋ฌผ์งˆ์„ ์ฒœ์—ฐ๋ฌผ๋กœ๋ถ€ํ„ฐ ์ฐพ์•„๋‚ด ๋ ค๋Š” ์—ฐ๊ตฌ๊ฐ€ ํ™œ๋ฐœํ•˜๊ฒŒ ์ง„ํ–‰๋˜๊ณ  ์žˆ์œผ๋ฉฐ, ์น˜๋ฃŒํšจ๊ณผ์— ๋Œ€ํ•œ ๊ด€ ์‹ฌ์ด ๋†’์•„์ ธ ์ด์— ๋Œ€ํ•œ ์ˆ˜์š”๋„ ์ฆ๊ฐ€ํ•˜๊ณ  ์žˆ๋‹ค [5][6][7] . ์ ํ•˜์ˆ˜์˜ค (Polygoni Multiflori Radix, PMR)๋Š” ๋‹ค๋…„์ƒ ๋ฉ๊ตด ์„ฑ ์ดˆ๋ณธ์œผ๋กœ ๋งˆ๋””ํ’€๊ณผ์˜ ์‹๋ฌผ์— ์†ํ•œ๋‹ค.…”
unclassified